Miami-Dade County Juvenile Weapons Offenders Program (JWOP): a potential model to reduce firearm crime recidivism nationwide. Issue 1 (14th December 2020) - Soe-Lin, Hahn; Sarver, Anjali; Kaufman, Joyce; Sutherland, Marilyn; Ginzburg, Enrique
Abstract : Introduction: Youth firearm violence has been a growing problem in the USA. Several programs across the country aimed at reducing recurrent gun violence in this vulnerable population have published recidivism rates of 40% to 50%. For the past 18 years, the Juvenile Weapons Offenders Program (JWOP) in Miami-Dade County has provided a unique multidisciplinary intervention encompassing 100 hours of violence education, behavioral modification, and social mentoring. The present study defines its outcomes as a national model for youth firearm recidivism prevention. Methods: Retrospective analysis of Florida Juvenile Justice Department records from 2008 to 2016 defined a group of youths convicted of firearm-related crimes and subsequently enrolled in the program. Cohorts were those who demonstrated successful completion of the JWOP program versus those who partially completed the program. At 6 and 12 months after release, records were cross-referenced with Florida Department of Justice criminal record system to prospectively capture rates of new all-comer and firearm-specific criminal charges. Results: 215 youth were included in the prospectively followed cohort at 6 months and 163 youth followed at 12 months after release. The 6-month recidivism rate for any criminal charge was 20.1% for program completers versus 32.9% for those who did not complete the program (p=0.047). When excluding unarmed criminal offenses, the recidivism rate dropped to 10.1% versus 22.4%, respectively (p=0.008). At 12 months, all-comers recidivism was 33.6% for the GATE program completion cohort versus 50% for the incomplete cohort (p=0.045). When excluding unarmed offenses, the recidivism rates were 18.6% versus 33.9%, respectively (p=0.035). Conclusion: The JWOP program has one of the lowest recidivism rates for reoffense for firearm and non-firearm-related offenses. Further investigation into details of the program's efficacy and its applicability for expansion to other state and national jurisdictions should serve a model for decreasing youth gun violence across the country.